2016
DOI: 10.3390/rs8100876
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Climate Change and Human Activities on Vegetation Dynamics in the Qinghai-Tibet Plateau

Abstract: Grasslands occupy nearly three quarters of the land surface of the Qinghai-Tibet plateau (QTP) and play a critical role in regulating the ecological functions of the QTP. Ongoing climate change and human interference have greatly affected grasslands on the QTP. Differentiating human-induced and climate-driven vegetation changes is vital for both ecological understanding and the management of husbandry. In this study, we employed statistical analysis of annual records, various sources of remote sensing data, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
154
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(168 citation statements)
references
References 78 publications
13
154
1
Order By: Relevance
“…Zhu, Zhang, et al () conducted a field experiment in a Tibetan alpine meadow and found warming caused a seasonal shift of ecosystem C exchange. Huang et al () verified that the vegetation dynamics in the TP were influenced by climate and human activities. Areas dominated by human activities are much smaller than those dominated by climate.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu, Zhang, et al () conducted a field experiment in a Tibetan alpine meadow and found warming caused a seasonal shift of ecosystem C exchange. Huang et al () verified that the vegetation dynamics in the TP were influenced by climate and human activities. Areas dominated by human activities are much smaller than those dominated by climate.…”
Section: Introductionmentioning
confidence: 99%
“…From these results, it seems that temperature is inhibiting the growth of vegetation. However, it is well known that this phenomenon occurs in arid and semi-arid areas, with less precipitation [22]. The total precipitation in Beijing is 500-600 mm per year, which makes Beijing a semi-humid region.…”
Section: Possible Influential Factors For Vegetation Change Trendsmentioning
confidence: 99%
“…Sun et al and Huang et al concluded that temperature and precipitation are both significant in impacting vegetation variation with high spatial and temporal heterogeneity, and that temperature exhibits a negative influence, while precipitation exhibits a positive influence on vegetation in the Tibetan Plateau based on the Normalized Difference Vegetation Index (NDVI) [22,23]. With the growing population and economy, many studies have gradually concluded that the human-induced activities are the dominant factors affecting vegetation greening and browning.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, regional vegetation dynamics are related closely to changes in local climate conditions and human activities [4][5][6]. However, it is difficult to distinguish the influence of these two driving factors when both function in the process of vegetation growth [7].…”
Section: Introductionmentioning
confidence: 99%